Pengaruh Komite Audit Dan Kepemilikan Asing Terhadap Nilai Perusahaan Yang Dimediasi Oleh Sustainability Report - Holly, Anthony; Tangke, Paulus; Jao, Robert; Tanri, Eveline Pricilia (FEB-Telkom University Publisher, 2024)
The purpose of this study is to examine the effect of audit committee, foreign ownership, and sustainability reports on firm value, and examine the effect of audit committees and foreign ownership on firm value mediated by sustainability reports.This study uses agency theory which explains the agency relationship between principals and agents, as well as stakeholder theory which explains the relationship between companies and their stakeholders. This study uses a purposive sampling method, namely a sample selection method that meets predetermined criteria so that the number of samples that meet the criteria is 33 companies for each period from the entire population of non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. The data analysis method used in this study is path analysis and mediation hypothesis testing using the sobel test. The results of this study indicate that the audit committee has a positive and significant effect and foreign ownership has a positive but not significant effect on the sustainability report. The audit committee has a positive but not significant effect on firm value, and foreign ownership and sustainability report have a positive and significant effect on firm value. This study also shows that sustainability reports are able to mediate the effect of audit committees on firm value, while sustainability reports are not able to mediate the effect of foreign ownership on firm value. Keywords : Foreign Ownership, Audit Committee, Firm Value, Sustainability Report